2021
DOI: 10.1037/pspa0000277
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiently complimentary?: Underestimating the positive impact of compliments creates a barrier to expressing them.

Abstract: Compliments increase the well-being of both expressers and recipients, yet people report in a series of surveys giving fewer compliments than they should give, or would like to give. Nine experiments suggest that a reluctance to express genuine compliments partly stems from underestimating the positive impact that compliments will have on recipients. Participants wrote genuine compliments and then predicted how happy and awkward those compliments would make recipients feel. Expressers consistently underestimat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 64 publications
3
34
0
Order By: Relevance
“…First, we contribute to the literature demonstrating that interaction partners are often focused on different aspects of an experience, which can subsequently lead to misalignment in judgment and suboptimal decision-making (Boothby et al, 2018;Kupor et al, 2017;Liu & Min, 2020;Zhang & Epley, 2012). We also note that past related work, which did not find a mediating role for surprise, measured surprise in terms of whether receiving the message and the specific content of the message itself was differentially surprising in magnitude based on perspective (Kumar & Epley, 2018;Zhao & Epley, 2021a). By contrast, our theorized mediator is a differential focus on the responder's surprise.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…First, we contribute to the literature demonstrating that interaction partners are often focused on different aspects of an experience, which can subsequently lead to misalignment in judgment and suboptimal decision-making (Boothby et al, 2018;Kupor et al, 2017;Liu & Min, 2020;Zhang & Epley, 2012). We also note that past related work, which did not find a mediating role for surprise, measured surprise in terms of whether receiving the message and the specific content of the message itself was differentially surprising in magnitude based on perspective (Kumar & Epley, 2018;Zhao & Epley, 2021a). By contrast, our theorized mediator is a differential focus on the responder's surprise.…”
Section: Discussionmentioning
confidence: 67%
“…For instance, people expressing gratitude underestimated how positive and surprising an expression of gratitude would be for a receiver and overestimated how awkward it would be (Kumar & Epley, 2018). Relatedly, research on compliments has shown that people offering compliments-which say something positive about a recipient's traits or behavior-underestimated the positive impact of their compliments on recipients (Boothby & Bohns, 2021;Zhao & Epley, 2021a, 2021b. Such misestimations are also explained by expressors' failure to sufficiently adjust from their own perspective to the recipient's perspective (Epley et al, 2004(Epley et al, , 2006.…”
Section: Mispredictions As a Function Of Perspective Differencesmentioning
confidence: 99%
See 3 more Smart Citations